Customization of CAD Modelling Software Using Parametric Macros for Design of Machinable Artistic Surface Patterns - Srivastava, Rahul (My University, 2009)
The design of the artistic feature involves various aspects such as analysis, creativity, and development. The craft work cannot be completed without the manual operations because such workmanship is the outcome of the some special skills owned by the artisans or craftsman. The initial canvas or the base parts required for craftwork are produced using some simple hand tools or manual machine tools as in case of wooden handicraft. As a result it takes considerable amount of time to carve the required base geometry of the part on which finally hand carving is done to generate the final product. The final outcome of the craft work is some specialized items and the number of finished pieces is generally very less. Because of this reason most of the craftsmen prepare the rough canvas for their work themselves than going in for some kind of automation solution. In the present work a attempt has been made to develop three dimensional model of a specific variety of parametric Rangoli and Phulkari pattern. The MACRO has been developed to generalized the parametric patterns and to allow the user to develop these types of design features with minimum requirement of expertise in this field. Solid modeling systems are design with an API (Application Programming Interface) which form the canvas for writing MACRO. The API of Solidwork solid modeler has been used for this purpose. The API provides the entire tool required to write and test this MACRO. The MACRO issue geometric instruction to the solid modeler based on parameter provided by user. The geometric instructions are then used to form a solid model of 3D design. Thus the MACROS has been created with a view of providing simple numeric parameter input which could be given on the web interface.Thus making the CAD model in the background on a remote server which has solid modelling software loaded. This reduces the cost of design creation by articians working on a web-page, rather it divides the cost of one CAD system amongst all remote users. The validation of the parameterized design has been done in solidwork®. The artistic patterns created and parameterized are checked for machinability on a 3-axis milling lathe. These parts are pseudo-symmetric sculptured surfaces on a cylindrical base. The parametric variation of the artistic design patterns are checked for machining on PBG2048 CNC milling lathe,which has been discussed in the thesis.
M.E. (CAD/CAM and Robotics Engineering- MED)
Keywords: CAD/CAM; API